(untitled) (Indian Journal of Arid Horticulture, 2025)
Mosaic disease, caused by the cucumber mosaic virus, is a significant threat to watermelon production in the arid and semi-arid regions of India. Screened 13 watermelon genotypes for tolerance to mosaic disease under open field conditions during the summer season of 2021 ICAR-Central Institute for Arid Horticulture, Bikaner. Among the 13 watermelon genotypes, none was found to be immune or highly resistant to mosaic disease. However, seven genotypes-AHW/BR-1, AHW/ BR-13, AHW/BR-16, AHW/BR-37, AHW/BR-5, AHW/BR-7, and AHW/BR-11 were classified as moderately resistant, with disease indices (PDI) ranging from 12.36% to 21.38%.